Deviations in the Initial Public Offering (IPO) Process as the Root of Stock Price Manipulation: A Case Study of Issuers in Indonesia for the 2020–2025 Period - Dewa Putu Yohanes Agata L. Sandopart; Lie Adek; Dewa Ayu Indiana Ida Loemongga Sandopart; Erma Wijayanti (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study analyzes deviations in the Initial Public Offering (IPO) process as the root of stock price manipulation among issuers in Indonesia for the 2020-2025 period. Using a qualitative approach with a multiple case study method, this research examines three issuers sanctioned by the Financial Services Authority (OJK): PT Berkah Beton Sadaya Tbk (BEBS), PT Repower Asia Indonesia Tbk (REAL), and PT Multi Makmur Lemindo Tbk (PIPA). Data were collected through in-depth interviews with 12 informants consisting of former OJK/Indonesia Stock Exchange (IDX) officials, capital market practitioners, academics, investigative journalists, and legal practitioners, as well as document analysis of prospectuses, financial statements, and OJK documents. The results identify four forms of IPO deviations: manipulation of material fact information, share allotment engineering, due diligence procedure violations, and discrepancies in the use of IPO funds. The BEBS case demonstrates how IPO deviations create structural conditions that facilitate pump-and-dump schemes through 57 nominee accounts, generating manipulative profits of IDR 14.5 trillion. This study identifies five factors causing weak detection and prevention: regulatory factors, law enforcement, corporate governance, market structure, and economic incentives. These findings confirm the OJK's statement that the root of stock price manipulation originates from deviations in the IPO process and emphasize the need for stronger supervision and enforcement.